Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques

Trente - Darsigny, Marie (Les éditions du remue-ménage, 2018)
Trente, un nombre qui n’arrivera jamais et s’il arrive, je l’éviterai, comme j’ai une fois évité un chevreuil en conduisant sur la route, le chevreuil courait devant mon auto, à gauche il y avait la rivière et à droite il y avait le fossé, c’est beau la Montérégie, au lieu de choisir l’un ou l’autre il continuait d’avancer droit devant, puis il a fini par bondir vers le fossé. Moi j’aurais choisi l’eau et d’ailleurs, à chaque fois que j’empruntais ce chemin-là, ça me chicotait de savoir que juste un petit coup de volant pouvait m’envoyer dans la rivière, un jour on est en vie et un jour on ne l’est plus, c’est tout.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discours dominant; fem3500; féminisme pop; premier cycle; périodes historiques; québec; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France), attitudes performatives; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Les Presses du réel, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Miss representation (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Place: San Francisco, Calif.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis